SUPERVISI PENDIDIKAN AGAMA ISLAM (Pembinaan Guru Agama Madrasah / Sekolah) - Abu Bakar (Lembaga penelitian dan pengabdian kepada Masyarakat, 2011)
Islam education supervision, having task does operation, estimation and menilik or mensupervisi to good Islam education at schooled Common and also Islam institution. Despitefully Supervises education also constitute applicable tricks in give service and construction to teacher deeping to perform its duty assignment at Madrasah / School in effort reaches education aim already be established effectively and efesien.